PERAN KEPEMIMPINAN TRANSFORMASIONAL, KEPUASAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA APARATUR SIPIL NEGARA DILINGKUNGAN BALAI LATIHAN KERJA DAN PENGEMBANGAN PRODUKTIVITAS DIY - Iwan Kurniawan (UPAJIWA, 2019)
Performance of employees cannot be separated from the resources owned by the organization, resources driven or executed by employees who play an active role as an actor in an effort to achieve organizational goals. This study aims to analyze the contribution of transformational leadership variables, work motivation and job satisfaction to the performance of State Civil Apparatus (ASN) within the Work Training and Productivity Development Center of Yogyakarta, either partially or simultaneously. This study uses quantitative approach with a sample of 48 respondents State Civil Apparatus (ASN) environment Yogyakarta Institute of Work Training and Productivity Development. The analysis technique used is path analysis. The results of the study found that transformational leadership had no significant effect on performance through work motivation in the Center for Work Training and Productivity Development in Yogyakarta. This study also found that job satisfaction has a positive and significant effect on performance through work motivation in the Center for Work Training and Productivity Development in Yogyakarta Keyword: Performance, transformational leadership, and work motivation